Impact of HR-HPV infection on oncological outcomes in early cervical cancer - Su, Xiaoqiang; Liu, Pan; Zhao, Hongwei; Sun, Lixin; Wang, Wuliang; Jin, Shuanglin; Wang, Hui; Liu, Ping; Chen, Chunlin; Hao, Min (Frontiers in Oncology, 2023)
Background: This study aimed to investigate the differences in long-term oncological outcomes between high-risk human papillomavirus (HR-HPV) negative and HR-HPV positive early-stage cervical cancers.We retrospectively analysed 2061 cases of early-stage cervical cancer from the Chinese cervical cancer clinical diagnosis and treatment database. Kaplan-Meier curves were used to describe the survival outcomes of different HR-HPV infections. Cox proportional hazard regression model was used to analyze and determine independent risk factors.Results: K-M analysis revealed no significant difference in 5-year OS between HR-HPV negative and HR-HPV positive groups (OS: 95.0% vs.95.6%, P=0.900). A significant difference was observed in 5-year DFS between the HR-HPV negative and HR-HPV positive groups (DFS: 87.2% vs.91.9%, P=0.025). Cox proportional hazard regression model indicated that HR-HPV infection (negative vs. positive) was an independent factor influencing 5-year DFS after early cervical cancer surgery (DFS: hazard ratio [HR]=1.862, P=0.022). HR-HPV infection (negative vs positive) was not an independent factor influencing 5-year OS after early cervical cancer surgery (OS: P=0.813). After 1:1 PSM This is a provisional file, not the final typeset article pairing, there was no significant difference in 5-year OS and DFS between HR-HPV negative group and HR-HPV positive group (OS: 91.6% vs.95.0%, P=0.297; DFS: 87.2% vs.85.1%, P=0.758). Cox multivariate analysis indicated that HR-HPV infection was not an independent factor influencing 5year OS and DFS after early cervical cancer surgery (OS: P=0.806, DFS: P=0.251).The tumour results of HR-HPV negative group and HR-HPV positive group were similar, after eliminating the differences in known variables that affect the oncological outcomes of cervical cancer. The treatment plan of HR-HPV positive cervical cancer is suitable for HR-HPV negative cervical cancer.